The Spanish Republican exile of 1939and his contributions to the development of Mexico - Jorge De Hoyos Puente (Ибероамериканские тетради, 2018)
This text realizes a revision to the contributions of the Spanish Republican exile in Mexico. We can see the evolution of the Spanish Republican exile in the country of reception. The article studies the particularities of an exile of long duration that determined the relations between Spain and Mexico for forty years.